Autophagy is activated in human spermatozoa subjected to oxidative stress and its inhibition impairs sperm quality and promotes cell death. Issue 4 (8th February 2022) - Uribe, Pamela; Meriño, Juan; Matus, Carola E; Schulz, Mabel; Zambrano, Fabiola; Villegas, Juana V; Conejeros, Iván; Taubert, Anja; Hermosilla, Carlos; Sánchez, Raúl
Abstract: STUDY QUESTION: Does oxidative stress (OS) activate autophagy in human sperm? SUMMARY ANSWER: Human spermatozoa subjected to OS activate an autophagic response. WHAT IS KNOWN ALREADY: Autophagy is a regulated pathway of lysosomal degradation which helps eukaryotic cells to maintain or restore homeostasis, being a cellular stress response mechanism. OS is a main cause of impaired sperm function and is linked to male infertility; however, whether OS activates autophagy in human spermatozoa is unknown. STUDY DESIGN, SIZE, DURATION: Human spermatozoa were exposed separately to ionomycin and hydrogen peroxide in order to induce OS. An untreated control group was included. Sperm cells under OS were then exposed to chloroquine in order to block autophagy. An untreated control and a control incubated only with the OS inducer were included in each experimental setting. PARTICIPANTS/MATERIALS, SETTING, METHODS: For this study, semen samples from normozoospermic donors were used and motile sperm cells were selected by the swim up technique. First, the generation of OS under our experimental conditions was demonstrated by analyzing sperm parameters including viability, reactive oxygen species (ROS) production, mitochondrial membrane potential (ΔΨm) motility and thiol oxidation. Then, proteins involved in autophagy, including the microtubule-associated protein light chain 3 (LC3), particularly LC3-I and LC3-II, autophagy-related 5 (ATG5) and autophagy-related 16 (ATG16) proteins as well as the phosphorylated form of AMP-activated protein kinase (pAMPK) were evaluated in spermatozoa exposed to OS and compared to the untreated control. Finally, the impact of autophagy blocking by chloroquine treatment on sperm quality, metabolic parameters, including glycolysis and oxidative phosphorylation, as well as the cell death markers phosphatidylserine externalization and caspase activation was analyzed. Sperm quality parameters, cell death markers and autophagy-related proteins were analyzed by flow cytometry. Motility was evaluated by the computer-assisted sperm analysis system and metabolic parameters were analyzed using an extracellular flux analyzer. MAIN RESULTS AND THE ROLE OF CHANCE: Exposure to ionomycin and hydrogen peroxide promotes OS resulting in increased ROS production and decreased viability, ΔΨm and motility, while increasing thiol oxidation. These alterations were accompanied by a decrease in LC3-I, indicating that autophagy was activated upon OS exposure. Ionomycin also caused an increase in LC3-II, ATG5, ATG16 and pAMPK content. Autophagy blocking of sperm exposed to OS caused deterioration in sperm quality and metabolic parameters as well as an increase in cell death markers. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: The study was carried out in vitro using motile sperm from normozoospermic donors; tests on sperm from infertile patients were not carried out. The autophagy blocking plus OS might generate a non-specific response to a highly stressful situation leading to the induction of cell death. WIDER IMPLICATIONS OF THE FINDINGS: Human spermatozoa subjected to OS activate an autophagic response and its blockage results in increased oxidative damage and commits spermatozoa to cell death. These results suggest a crucial role of autophagy as a stress response by male gametes, which contributes to maintaining the functionality and lifespan of ejaculated sperm cells. Detection of autophagy activation in sperm cells ex vivo could be included in semen analysis as a marker of OS, especially in men displaying high levels of seminal ROS. Novel strategies that aim to activate this cellular stress response could improve sperm quality/functionality under natural ejaculate conditions in which increased ROS levels are expected. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Fondo Nacional de Investigación Científica y Tecnológica, Chile (ANID/FONDECYT, Grant number 11170758 to P.U.); the Comisión Nacional de Investigación Científica y Tecnológica, Chile (ANID/CONICYT, Grant number PAI79160030 to P.U.) and the Dirección de Investigación, Universidad de La Frontera. The authors disclose no potential conflicts of interest.